Knowledge, attitudes, perceptions, and economic valuation of Philippine tarsier a case in Biliran, Biliran, Philippines - de la Cruz, John O.; Subade, Rodelio F. (2023)
Philippine tarsiers are specially protected faunal species of the Philippines. There is an absence of literature on the economic value of Philippine tarsier and very few studies involving knowledge, attitudes, and perceptions of the small primate exist. In response, this study provides more insights on the locals' knowledge, attitudes, and perceptions, and initial information on the economic valuation of Philippine tarsiers based on a survey of 420 households from March to April 2023 in Biliran, Biliran where this shy primate is also naturally found. In general, the households in Biliran possessed strong environmental attitudes (87.38%), were generally aware of the Philippine tarsier existence (~69%), and held non-zero economic value (parametric mean WTP= Php2,371.95; non-parametric mean WTP = Php764.12) for the primate and its habitat. However, the locals' knowledge of Philippine tarsier is limited, which needs to be addressed to improve their treatment and perceptions of the roles, usefulness, and population endangerment risk of the primate. The households were also receptive to the proposition of establishing the upland forest of Biliran as a local conservation area or a critical habitat for Philippine tarsier based on the high number of respondents who expressed their willingness to support (~86%) and willingness to pay (~78%) the proposed conservation program. While the proposed Philippine tarsier conservation program offers promising results, it is urgent to address the most pressing problems and recognize emerging issues that may adversely affect the initiative. This predicament justifies the need for drafting and implementing informed Philippine tarsier conservation policies.
Graduate thesis (M.S. Environmental Science) --University of the Philippine, Tacloban.